The Effect of Demand, Convenience, Interactivity, Playfulness Through Impulsive Buying as an Intervening Variable on Shopee Live - Uswatun Khasanah; Arif Kuswanto (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Lifestyles and patterns of people's behavior in everyday life have been influenced by technology that is currently developing rapidly which is followed by the use of the internet, especially in online trading, especially in purchasing products through ecommerce. Technology and innovation have changed the way buyers and sellers engage in market exchanges. Live streaming has become a new medium for e-commerce marketing. Shopee is the number 1 e-commerce in Indonesia followed by the number 1 Shopee Live feature in Indonesia which is widely accessed. With the new trend of shopping through live streaming, the aim of this research is to analyze the influence demand, convenience, interactivity, playfulness to impulsive buying through perceived enjoyment Shopee Live in the Indonesian region. This study uses a quantitative approach with descriptive analysis. The sampling technique used is non-probability sampling with 400 respondents with a Likert scale. The data analysis method used is partial least square on SmartPLS 3.0 software. The results of this study are variable demand (X1) has a positive and significant effect on variables perceived enjoyment (Z) and impulsive buying (Y) mediated by perceived enjoyment (Z), variable convenience(X2) has a positive and not significant effect on variables perceived enjoyment with impulsive buying (Y) mediated by perceived enjoyment (Z), variable interactivity (X3) has a positive and not significant effect on variables perceived enjoyment (Z) dan impulsive buying (Y) mediated by perceived enjoyment(Z), variable playfulness (X4) has a positive and significant effect on variables perceived enjoyment (Z) and against impulsive buying (Y) mediated by perceived enjoyment (Z), variable perceived enjoyment (Z) has a positive and significant influence on impulsive buying.